Implementation of independent audio mixing control using AoIP. (June 2020) - Lee, Jaeho; Park, Jaewook; Lee, Jiyoun; Kwon, Soonchul; Lee, Seunghyun
Abstract: Recently, the media of the signal transmission of pro-audio equipment has been changed from audio cable to LAN cable. As the transmission of audio signal by LAN cable solves the problem of the loss and noise caused by long distance transmission, various transmission technologies are emerging. Particularly, some technologies change the configuration of the conventional sound system by mixing different audio sources in the receiving device, including the function of the signal transmission. However, these technologies can only be implemented in the Intranet; even if they are implemented in the Internet, each receiving device has limited independent mixing. In this paper, each receiver based on the Internet selects, controls, and mixes multiple audio sources. Consequently, it is possible to provide an acoustic environment suitable for a user's taste rather than a uniform sound service. The results of this study show that each receiver selects, controls, and mixes the different audio sources independently, and then outputs these audio sources. It is expected that this study will become the standard in the related industry as a new audio network protocol in the field of Audio Service.